2019
DOI: 10.1002/app.48156
|View full text |Cite
|
Sign up to set email alerts
|

Polymer brushes on graphene oxide for efficient adsorption of heavy metal ions from water

Abstract: The pollution of heavy metal ions in water poses a serious threat to human being and ecosystems. Here, we report polyamidoxime (PAO) brush grafted graphene oxide (GO) as a highly efficient adsorbent for extraction of toxic metal cations from water. Surface-initiated atom transfer radical polymerization was used to grow polyacrylonitrile (PAN) brushes on GO, followed by conversion of the nitrile groups in PAN into amidoxime groups, which had high binding affinity toward heavy metal cations. The PAO brush grafte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(30 citation statements)
references
References 85 publications
0
28
0
Order By: Relevance
“…instrument (Thermo Fischer Scientific, Inc., Waltham, MA, USA) that was calibrated using Ag 3d 5/2 line (0.45 eV) and C 1s line (0.82 eV). The pH PZC was obtained using the pH-drift method [45]: a fixed amount of sorbent (100 mg) was stirred for 48 h with 50 mL of 0.1 M NaCl solutions at different initial pH values (pH 0 , in the range [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. The equilibrium pH was measured with a S220 Seven Compact pH/ Ionometer.…”
Section: Characterization Of Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…instrument (Thermo Fischer Scientific, Inc., Waltham, MA, USA) that was calibrated using Ag 3d 5/2 line (0.45 eV) and C 1s line (0.82 eV). The pH PZC was obtained using the pH-drift method [45]: a fixed amount of sorbent (100 mg) was stirred for 48 h with 50 mL of 0.1 M NaCl solutions at different initial pH values (pH 0 , in the range [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. The equilibrium pH was measured with a S220 Seven Compact pH/ Ionometer.…”
Section: Characterization Of Materialsmentioning
confidence: 99%
“…Chemically modified minerals were also efficiently designed for metal sorption [12]. New materials have been recently developed for increasing sorption capacities or improving uptake kinetics such as polymer brushes [11,13] or metal organic frameworks (MOFs) [14]. Functionalized activated carbons and multi-walled carbon nanotubes have also retained attention for the last decades [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Another report showed the possibility to control chain length and grafting density of polystyrene brushes obtained using ATRP on graphene nanosheets [ 20 ]. Liu et al [ 21 ] reported the preparation of GO decorated with poly(amidoxime) brushes by grafting poly(acrylonitrile) chains via surface-initiated ATRP (SI-ATRP) and subsequent formation of amidoxime groups from the nitrile ones. Zygo et al [ 22 ] showed modifications of the GO surfaces by selected poly(methacrylates) at various grafting densities.…”
Section: Introductionmentioning
confidence: 99%
“…Although a lot of applications have been achieved in the fields of nanooptics, nanofluidic, nano-electronic devices and so on [62,63], more and more novel applications needed to be discovered in the future so that the TBN method can be used in industrial engineering as early as possible. Moreover, AFM exhibits a huge potential in the development of polymer technology, especially for the emerging field of “polymer brushes”, which is a technique that grafts polymers on to solid substrates [64] and has been applied in the field of sewage purification [65], adsorption of charged biomolecules [66], lubrication [64], adhesion [67], colloidal stability [68] and biotechnology [69]. However, there is also a problem that the desorption of chains during and after the brush creation remains a common phenomenon by the existing method [68], and therefore, a reliable approach is required.…”
Section: Introductionmentioning
confidence: 99%